Recent trends in computational intelligence and its application : proceedings of the 1st International Conference on Recent Trends in Information Technology and Its Application (ICRTITA, 22) /: proceedings of the 1st International Conference on Recent Trends in Information Technology and Its Application (ICRTITA, 22). (2023) - Unknown
No abstract available